Effectiveness of Smart Counting in Improving Addition and Subtraction Skills in Early Childhood - Ibnu Imam Al Ayyubi; Ari Limay Trisno Putra; M. Baihaki Hidayatulloh (Sekolah Tinggi Ilmu Tarbiyah Bustanul 'Ulum Lampung Tengah, 2025)
Mathematics is a fundamental aspect that must always be developed. Mathematical ability is crucial for early childhood because it can develop logical conceptual understanding and problem-solving skills. In this case, mathematical skills in early childhood not only strengthen numerical understanding but also broader cognitive understanding. This study used a quantitative method with an experimental approach involving one pretest-posttest group, without a control group.This study aims to evaluate the effectiveness of the Smart Counting method in improving understanding of addition and subtraction operations in early childhood. Using a quantitative approach with a pre-experimental design, the study involved 30 participants from RA Assyafiq, West Bandung Regency. Results showed a significant improvement in basic maths comprehension, with a mean pretest of 51.87 and posttest of 63.73 (p < 0.05). The Smart Counting method, which combines interactive technology and educational games, is proven to make learning more concrete and fun. Nonetheless, challenges such as the digital divide and lack of teacher training need to be addressed to maximise the effectiveness of this method. This research is expected to contribute to the development of innovative learning methods for early childhood, as well as encourage collaboration between the government, educational institutions, teachers and parents in its implementation.